Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil - Costa, Wilson J.e.m. (Zootaxa, 2004)
Simpsonichthys suzarti, new species, from the floodplains of the lower Rio Pardo, northeastern Brazil, is described. It is a member of a clade, herein termed S. constanciae species group, which is diagnosed by the eyes laterally positioned on the head and a derived pattern of cephalic neuromast arrangement, in which the supraorbital series is interrupted by a median interspace. It differs from all other species of the group in having the anal fin rounded in males and by the distinctive color pattern of males, including the presence of reddish brown bars along the whole flank, reticulate dark brown marks on the dorsal fin and oblique dark brown bars on the anal fin. A key to the species of the S. constanciae group is provided.